ANALISIS PERILAKU INVESTASI DITINJAU DARI BEHAVIORAL INTENTION DAN FINANCIAL LITERACY - Viska Putria Ananda; Dheri Febiyani Lestari; Della Apriani; Muhamad Zulfikar Bintang Satrio (LP2M Universitas Perjuangan Tasikmalaya, 2025)
The objectives of this study was to determine and analyze the description of behavioral intention, financial literacy, and investment behavior in Generation Z in Tasikmalaya City, as well as the influence of behavioral intention and financial literacy on investment behavior in Generation Z in Tasikmalaya City. The research method used in this study is the survey method, while the types of data used in this study are primary data and secondary data. The object of this study is Generation Z investors in Tasikmalaya City, with a research sample of 100 respondence and using sampling technique the non-probability sampling method. The data analysis technique used is multiple regression analysis. The results of the study indicate that behavioral intention, financial literacy, and investment behavior in Generation Z in Tasikmalaya City are included in the good category. The test results prove that behavioral intention and financial literacy simultaneously and partially have a significant effect on investment behavior in Generation Z in Tasikmalaya City.